Transitions in Metabolic Risk and Long‐Term Cardiovascular Health: Coronary Artery Risk Development in Young Adults (CARDIA) Study. Issue 10 (October 2016) - Murthy, Venkatesh L.; Abbasi, Siddique A.; Siddique, Juned; Colangelo, Laura A.; Reis, Jared; Venkatesh, Bharath A.; Carr, J. Jeffrey; Terry, James G.; Camhi, Sarah M.; Jerosch‐Herold, Michael; de Ferranti, Sarah; Das, Saumya; et al.
Abstract : Background: Despite evidence suggesting that early metabolic dysfunction impacts cardiovascular disease risk, current guidelines focus on risk assessments later in life, missing early transitions in metabolic risk that may represent opportunities for averting the development of cardiovascular disease. Methods and Results: In 4420 young adults in the Coronary Artery Risk Development in Young Adults (CARDIA) study, we defined a "metabolic" risk score based on components of the Third Report of the Adult Treatment Panel's definition of metabolic syndrome. Using latent class trajectory analysis adjusted for sex, race, and time‐dependent body mass index, we identified 6 distinct metabolic trajectories over time, specified by initial and final risk: low‐stable, low‐worsening, high‐stable, intermediate‐worsening, intermediate‐stable, and high‐worsening. Overall, individuals gained weight over time in CARDIA with statistically but not clinically different body mass index trend over time. Dysglycemia and dyslipidemia over time were highest in initially high or worsening trajectory groups. Divergence in metabolic trajectories occurred in early adulthood (before age 40), with 2 of 3 individuals experiencing an increase in metabolic risk over time. Membership in a higher‐risk trajectory (defined as initially high or worsening over time) was associated with greater prevalence and extent of coronary artery calcification, left ventricular mass, and decreased left ventricular strain at year 25. Importantly, despite similar rise in body mass index across trajectories over 25 years, coronary artery calcification and left ventricular structure and function more closely tracked risk factor trajectories. Conclusions: Transitions in metabolic risk occur early in life. Obesity‐related metabolic dysfunction is related to subclinical cardiovascular phenotypes independent of evolution in body mass index, including coronary artery calcification and myocardial hypertrophy and dysfunction.